PROSES PRODUKSI FRUIT ELEVATOR KAPASITAS 30 TON DI PMT DOLOK HILIR - Manurung, Aldi Giovany Paulus (Fakultas Teknik dan Pengelolaan Sumberdaya Perairan Universitas HKBP Nommensen Pematangsiantar, 2025)
Field Work Practice (PKL) is an essential activity for students to apply the theories learned in the classroom into real working environments. Through PKL, students are required not only to master theoretical concepts but also to understand the mechanisms and operational systems in the field. This activity serves as a means to broaden knowledge, develop practical skills, and prepare students to face the challenges of the industrial world after completing their studies. The implementation of PKL at Pabrik Mesin Tenetra (PMT) provided direct experience with the production process and various machine components that play a crucial role in the palm oil industry. This industry holds a strategic position in Indonesia due to its high economic value products and significant contribution to the national economy. During PKL, I observed the production system from the initial stages to machine maintenance and the application of product quality standards that support the smooth operation of the factory. The main focus of this report is the Fruit Elevator, a component that acts as a material transfer link between stages in the palm oil processing system. The Fruit Elevator’s role is vital as it influences the overall smoothness of the production flow. Malfunction or disruption of this machine can lead to decreased productivity and product quality. Therefore, a detailed study of the design, working principle, and potential development of the Fruit Elevator is essential to support the efficiency and effectiveness of the palm oil production process.